2010
DOI: 10.1093/geronb/gbq033
|View full text |Cite
|
Sign up to set email alerts
|

Physical Health and Depression: A Dyadic Study of Chronic Health Conditions and Depressive Symptomatology in Older Adult Couples

Abstract: This study examined the associations among chronic health conditions, sociodemographic factors, and depressive symptomatology in older married couples. Data from the 2004 wave of the Health and Retirement Study (n = 2,184 couples) were analyzed. Results indicated a reciprocal relationship in depressive symptoms between spouses. Additionally, post hoc analyses indicated that husbands' stroke and high blood pressure were related to increased depressive symptomatology among wives. Beyond the reciprocal relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
69
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 40 publications
15
69
3
Order By: Relevance
“…Similarly, compared to men, women are more likely to experience decreased self-esteem and a negative impact of caring for their ill partner (Nijboer et al, 2000). Also, despite finding a reciprocal relationship between spouses' depressive symptoms, Ayotte et al (2010) found that women's depressive symptoms were affected by their husbands' health but men were not impacted by their wives' health.…”
Section: Gender Norms and Spousal Well-beingmentioning
confidence: 83%
See 1 more Smart Citation
“…Similarly, compared to men, women are more likely to experience decreased self-esteem and a negative impact of caring for their ill partner (Nijboer et al, 2000). Also, despite finding a reciprocal relationship between spouses' depressive symptoms, Ayotte et al (2010) found that women's depressive symptoms were affected by their husbands' health but men were not impacted by their wives' health.…”
Section: Gender Norms and Spousal Well-beingmentioning
confidence: 83%
“…For example, Ayotte, Yang, and Jones (2010) and Pruchno, Wilson-Genderson, and Cartwright (2009) found reciprocal relationships between older spouses' depressive symptomology. After accounting for various demographic, health, and social predictors of well-being, Goodman and Shippy (2002) found the same reciprocal relationship-when one older marital partner is depressed, the other partner also tends to be depressed.…”
Section: Emotional Contagion Of Spousal Well-beingmentioning
confidence: 99%
“…Within the context of an intimate relationship, studies find evidence that partners' well-being is correlated (Ayotte, Yang, & Jones, 2010;Peek, Stimpson, Townsend, & Markides, 2006;Townsend, Miller, & Guo, 2001). Studies have found significant spousal concordance in behaviors such as smoking, alcohol intake, weight gain, and even cardiovascular risk (Castelnuovo, Quacquaruccio, Donati, de Gaetano, & Iacoviello, 2008;Christakis & Fowler, 2008;Graham & Braun, 1999;Sobal, Rauschenbach, & Frongillo, 2003).…”
Section: Health Concordancementioning
confidence: 99%
“…One study found that wives were more likely to report higher levels of depressive symptoms if their husband was diagnosed with a chronic condition (Ayotte et al, 2010). These studies suggest the need for longitudinal analyses to examine the influence of SHSs on the mental and physical health trajectories of their partners.…”
Section: Health Concordancementioning
confidence: 99%
See 1 more Smart Citation